How climate change and insecurity pushed 5 million people to hunger in Chad, Africa - Shuaibu Saidu Musa; Tchindebe Bouri Ela; Emery Manirambona; Deborah Oluwaseun Shomuyiwa; Usman Abubakar Haruna; Don Eliseo Lucero‐Prisno III; Abdulrahman Muhammad (Wiley, 2022)
Abstract Climate change and insecurity pose challenges to food security around the globe. Chad has experienced several climate changes and insecurity influences on its food security, where, approximately 5 million people were pushed into hunger in the country. Desertification, flooding, and depletion of freshwater resources have pushed the country into hunger due to their negative effect on agro‐pastoral production in Chad. Insecurity due to the Boko‐Haram insurgency, in particular, has impaired agriculture, which is the mainstay of the country's economy. The influx of refugees from Nigeria and Cameroon has also compounded the hunger in Chad, as the country hosts the largest number of refugees in the region. Leveraging collaboration for climate change and improving security should be a priority for Chad. Increased consideration and action in the region can facilitate focus on climate change action in the region. International and multisectoral collaboration can set the pace for revamping the present security framework. Raising climate change awareness among key stakeholders and building capacity at the national level can help mitigate the impact of climate change on food security in Chad.